GNAS mutations are present in colorectal traditional serrated adenomas, serrated tubulovillous adenomas and serrated adenocarcinomas with adverse prognostic features. Issue 7 (22nd March 2017) - Liu, Cheng; McKeone, Diane M; Walker, Neal I; Bettington, Mark L; Leggett, Barbara A; Whitehall, Vicki L J
Abstract : Aims: Activating mutations in GNAS are important in the development of a range of neoplasms, including a small proportion of conventional adenomas and colorectal carcinomas (CRCs). However, their contribution to serrated pathway neoplasia is unclear, as mutations have only been examined in small series of sessile serrated adenomas (SSAs) and traditional serrated adenomas (TSAs), and not in serrated tubulovillous adenomas (sTVAs). The aim of this study was to investigate the frequency and significance of GNAS mutations in colorectal adenomas and CRCs. Methods and results: Using a large, well‐characterized series, we identified GNAS mutations in 9.2% (18 of 196) of TSAs, 7.1% (four of 56) of sTVAs and 2.0% (nine of 459) of CRCs. Mutations were absent in SSAs (none of 43), tubular adenomas (none of 50) and conventional tubulovillous adenomas (none of 50). A BRAF or KRAS mutation was seen in 77.4% of GNAS mutant lesions, suggesting a synergistic effect with the mitogen‐activated protein kinase pathway. In CRCs, GNAS mutations were associated with mucinous differentiation and serrated morphological features. Conclusions: GNAS mutations contribute significantly to the development of a subset of serrated adenomas and CRCs.